The effectiveness of reminiscence in cognition, depressive symptoms, and quality of life in elderly people in the community: a systematic review - Isabel Gil; Paulo Santos-Costa; Daniela Cardoso; Vitor Parola; Bobrowicz-Campos, E.; Maria de Lurdes Almeida; Apóstolo, João (Referência: revista de enfermagem, 2018)
Background: In the literature, reminiscence therapy (RT) stands out as a non-pharmacological intervention commonly implemented in groups of elderly people with cognitive impairment. Objective: To identify the best available evidence on the effectiveness of RT in cognition, depressive symptoms, and quality of life in elderly people using community support structures. Method of Review: The methodology proposed by the Joanna Briggs Institute was followed. Studies focused on group RT, including elderly people (≥ 65 years old) with cognitive impairment and using community support structures, were considered. Critical analysis, extraction, and synthesis of results were conducted by 2 independent researchers. Presentation and interpretation of results: Two randomized controlled trials and 2 quasi-experimental studies were included (n = 502); the heterogeneity of the studies precluded meta-analysis. Two studies evidenced the benefits of RT to cognition. None of the studies showed the positive impact of the intervention on depressive symptomatology. Regarding quality of life, inconsistent results were found. Conclusions: The RT seems to have a beneficial effect on improving cognition in elderly people with cognitive impairment in a community context.